ANSEIO POR DANÇAR DIFERENTE LEITURA POPULAR DA BÍBLIA NA ÓTICA DA HERMENÊUTICA FEMINISTA CRÍTICA DE LIBERTAÇÃO - Felix, Isabel Aparecida (2010)
The main objective of this research is to investigate the socio-religious potential of the popular reading of the Bible in function of transformation. In this research, we will analyze the thought of Carlos Mesters and its interpretation developed by the Center for Biblical Studies - CEBI. To reach our goal, we will work, particularly with two popular biblical readings, namely, "The way to Emmaus and The Popular Reading of the Bible: Searching for the Lost Coin , both used as a methodology for biblical reading within CEBI. These approaches of interpretation intend to go beyond the study of the biblical texts and seek to contribute to the process of conscientization towards transformation of the reality of domination and oppression. It is in this context that we study the critical feminist hermeneutics of liberation articulated by Elisabeth Schüssler Fiorenza, as an important tool to examine and dialogue with these popular approaches of reading. We relate the methodology of Cebi to a feminist and emancipatory paradigm of biblical interpretation. In addition to pedagogical and methodological issues, this enterprise results in the problematisation of some theological themes intrinsic to biblical interpretation, namely, the subject of interpretation, the analysis of reality and the criteria to define revelation and authority. From this dialogue between "popular reading of the bible" and "critical feminist hermeneutics of liberation , we come to the conclusion that the first, despite being defined as an approach to a liberating biblical interpretation shows some gaps in relation to this goal. From the analysis of the different methodological steps of interpretation and the theological themes, we perceive within Mesters´s project and more specifically in the project of CEBI, the absence of analytical tools which could facilitate the transformation of the concrete socio-religious realities, the analysis of the experiences of the subjects of interpretation, and the reflection on criterias to define the place of revelation and authority. The thesis is not intended to replace the popular method of Biblical reading by the hermeneutical dance proposed by Schüssler. The thesis instead tries to rethink the possibilities and problems of the popular biblical reading in its attempt to transform reality. In this sense, the dialogue with political emancipatory theories articulated theologically and biblically by Schüssler may be important for political and methodological reassessment of CEBI. (AU)